Integration of Local Wisdom in Contextual, Innovative, and Technology-Based Physics Learning - Yeni Kusmira; Syaiful Eddy; Lukman Hakim (Graduate Program Magister Manajemen Pendidikan, 2026)
This study aims to identify the diversity of local wisdom containing physics concepts, analyze the determinants of successful integration into physics learning, examine its impact on students’ learning outcomes, and formulate an adaptive learning model. This research employed a systematic literature review using the PRISMA approach. Articles were collected from Scopus, Google Scholar, DOAJ, and the Indonesian Publication Index (IPI). A total of 1,156 articles published between 2015 and 2025 were identified, and 79 articles met the inclusion criteria for thematic analysis. The findings revealed six dominant forms of local wisdom integrated into physics learning, namely gasing, rice pounding mortars, outrigger boats, bamboo bridges, angklung, and egrang. Five key determinants of successful integration were identified: educator capacity (β=0.305), learning resources (β=0.278), school policy support (β=0.254), digital technology access (β=0.231), and community participation (β=0.189). The study also formulated the Integrated Ethnoscientific Physics Learning Model (MoPEFET), consisting of local science identification, contextual and innovative learning design, technology-based enrichment, and continuous evaluation. The results indicate that integrating local wisdom positively contributes to students’ conceptual understanding, scientific literacy, learning motivation, and appreciation of cultural heritage. The model offers practical guidance for implementing culturally responsive and technology-supported physics learning.